The effects of altered sterol composition on the mitochondrial adenine nucleotide transporter of Saccharomyces cerevisiae. - Haslam, J M (1977)
1. The membrane sterol composition of mitochondria of the ole-3 mutant of Saccharomyces cerevisiae was manipulated by growing the organism in the presence of Tween 80 (1%, W/V) plus defined supplements o- delta-aminolaevulinate. 2. Changes in mitochondrial sterol content induced considerable changes in the adenine nucleotide transporter. 3. As the sterol content was decreased, the affinity of the transporter for ATP did not alter significantly, but the rate of ATP uptake was greatly decreased, the total number of atractylate-sensitive binding sites diminished, and the proportion of high-affinity binding sites was decreased. 4. Since sterol depletion also uncouples oxidative phosphorylation [Astin & Haslam (1977) Biochem. J., 166, 287-298] and prevents the intramitochondrial generation of ATP, the decrease in the rate of ATP uptake by sterol-depleted mitochondria will cause a decrease in intramitochondrial ATP concentrations in vivo. This probably explains the inhibition of mitochondrial macromolecular synthesis that has previously been reported in lipid-depleted yeast mitochondria.